Pendampingan pengolahan limbah kulit buah kolang kaling menjadi pupuk kompos di nagari Andaleh baruh bukik kabupaten tanah datar - Azhar, Zul; Putra, Hari Setia; Syamwil, Syamwil; Ardi, Zadrian (Universitas Negeri Padang, 2022)
Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Universitas Negeri Padang is responsible for providing guidance and imparting knowledge to the community, one of which is by conducting community service activities. One of the community service activities carried out was assistance in processing kolang kaling peel waste into compost in Nagari Andaleh Baruh Bukik, Tanah Datar Regency. Nagari, which is located in Sungayang District, has a superior commodity in the form of Nira Tree, where this sap tree also produces kolang kaling fruit. This activity is carried out based on the existing problems, namely that the community has not processed the kolang kaling fruit waste, even though the waste from this fruit has a high economic value. For this reason, assistance is provided to the community in processing kolang kaling peel waste into compost. In addition to protecting the environment, this economic value waste treatment is carried out so that people's incomes increase. This activity is carried out in several stages, namely socialization, training, assistance and procurement of tools. It is hoped that in the following year, activities can be continued in business management, packaging and sales.